Simulation, Science, and Stakeholders: Challenges and Opportunities for Modelling Solutions to Societal Problems. (31st March 2023) - Shults, F. LeRon
Abstract : The article outlines an approach to computer modelling called "human simulation, " whose development has been explicitly oriented towards addressing societal problems through transdisciplinary efforts involving stakeholders, change agents, policy professionals, subject matter experts, and computer scientists. It describes the steps involved in the creation and exploration of the "insight space" of policy-oriented artificial societies, which include both analysing societal problems and designing societal solutions. A case study is provided, based on an (ongoing) research project studying "emotional contagion" related to misinformation, stigma, and anxiety in the wake of the COVID-19 pandemic, along with lessons learned about some of the challenges and opportunities facing scientists and stakeholders trying to simulate solutions to complex societal problems.